A new heuristic algorithm to solve Circle Packing problem inspired by nanoscale electromagnetic fields and gravitational effects - Martínez Ríos, Félix Orlando; Marmolejo Saucedo, José Antonio; Murillo-Suarez, Alfonso (My University, 2018)
In this paper, we present a new algorithm for the fast and efficient solution of the Packing problem in two dimensions. The packing problem consists in finding the best arrangement of objects (many geometrical forms) in a specific space called container.This new algorithm is inspired by the observations of nanometric scale electromagnetic fields. We use the electromagnetic theory of the electric field to calculate the best position to place a circular object in a configuration of other circular objects previously packing. Also, in this new algorithm we simulate two processes called »gravity» and »shaken» that compact the distribution of the objects placed in the container and allow to minimize the unoccupied space. © 2018 IEEE.
Keywords: Gravitational algorithms; Nanoscale electromagnetic fields; Nature inspired algorithm; Optimization; Packing problem; Containers; Electric fields; Electromagnetic field theory; Heuristic algorithms; Nanotechnology; Object recognition; Circle packing problem; Circular objects; Electromagnetic theories